Graduate attributes: Social constructions and lived experience of university students in Ireland - EMON, AYESHAH; Timonen, Virpi (Journal of Education Culture and Society, 2019)
Aim. This paper examines how dominant understandings of students in third-level education in Ireland are reflected in national policies, filtered through the official and aspirational texts issued by Irish colleges, and negotiated and contested by students. Specifically, we investigate the discrepancies between the perceived needs of students in third-level education as imagined in government policies and promoted by higher education institutions, and the lived realities of students who grapple with multiple challenges brought about by structural failures in housing and higher education funding policy.Methods. Through documentary analysis and primary qualitative data on student experiences, we examine how the imagined figure of the third-level student/graduate becomes imbued with the aspirations of multiple stakeholders: policymakers, academic institutions, and potential employers - in ways that conflict with the lived realities of students.Results. We find that students are caught between the ambitions and expectations of an education system that pushes them into higher education without the requisite and adequate supports.Conclusion. The ideal graduate is expected to embody the nation’s hope for future success as well as to uphold the alma mater’s reputation among employers. Couched in this rhetoric of the graduate as the beacon of hope, however, are deeper failings of a welfare state that is still battling the aftermath of recession. These failures are projected onto students, manifesting in a very real way in their minds and lives as they struggle to balance between institutional, family and personal expectations, the demands of daily life and future plans.